2000
DOI: 10.1021/la000618m
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Nanosized Silica by in Situ Polymerization of tert-Butyl Acrylate Monomer

Abstract: Stable dispersions of nanosilica ranging in size between 8 and 11 nm were coated with tert-butyl acrylate polymer by in situ polymerization of monomer adsorbed on the particles in 2-propanol. The system was developed for use in the encapsulated inorganic resist technology. To achieve a high coating efficiency, silica was first modified with the 3-(trimethoxysilyl)propylmethacrylate (MPS) coupling agent at two different degrees of grafting. The presence of the bound MPS agent and of the polymer at the silica su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 20 publications
2
109
0
4
Order By: Relevance
“…The last one, also called by interfacial polymerization, will not be presented in this paper, spite of it been a well established method it is most used to trap inorganic particles and not necessarily improve their stability [27].…”
Section: Encapsulation Techniques Based On Chemical Nature Combinatiomentioning
confidence: 99%
“…The last one, also called by interfacial polymerization, will not be presented in this paper, spite of it been a well established method it is most used to trap inorganic particles and not necessarily improve their stability [27].…”
Section: Encapsulation Techniques Based On Chemical Nature Combinatiomentioning
confidence: 99%
“…It has already been shown that nanoparticles can be functionalized and homogeneously dispersed in an organic medium. [19][20][21] Care must be taken in functionalizing these nanoparticles since it is likely any addition of groups that will help disperse them in an organic fluid will also likely reduce the effective RI of the solution.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…[2]. In this regard, numerous polymer-based encapsulation techniques have been reported using different approaches to encapsulate various inorganic NPs, like silica, titania, alumina, calcium carbonate, carbon black, magnetic iron oxides, metal nanoparticles and quantum dots [3][4][5][6]. The controlled fabrication of well-defined micro-and nano-sized composites encapsulated in polymer matrices has become one of the main topics in materials science oriented towards bio-medical applications.…”
Section: Introductionmentioning
confidence: 99%